2000
DOI: 10.1136/gut.46.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate and glucose metabolism by colonocytes in experimental colitis in mice

Abstract: Background/aims-Impaired colonocyte metabolism of butyrate has been implicated in the aetiopathogenesis of ulcerative colitis. Colonocyte butyrate metabolism was investigated in experimental colitis in mice. (Gut 2000;46:493-499) Methods-Colitis was induced in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 36 publications
2
122
0
4
Order By: Relevance
“…In experimental colitis, colonocyte oxidation of butyrate is markedly suppressed (169) , leading to reduced cellular ATP levels and decreased cell metabolism. Many studies have demonstrated that delivery of butyrate through local enema or diet results in a protective or therapeutic effect against inflammatory bowel diseases (170,171) .…”
Section: Protecting Effect Against Inflammatory Intestinal Diseasesmentioning
confidence: 99%
“…In experimental colitis, colonocyte oxidation of butyrate is markedly suppressed (169) , leading to reduced cellular ATP levels and decreased cell metabolism. Many studies have demonstrated that delivery of butyrate through local enema or diet results in a protective or therapeutic effect against inflammatory bowel diseases (170,171) .…”
Section: Protecting Effect Against Inflammatory Intestinal Diseasesmentioning
confidence: 99%
“…Many of the protective functions of the bacteria linked to IBD relate to their ability to ferment dietary fibre to produce short-chain fatty acids (SCFA) [98]. SFCA are a key source of energy for colonic epithelial cells [99], and regulate colonic regulatory T cell homeostasis [100]. In ileal CD, the abundance of members of the family Ruminococcaceae, in particular Faecalibacterium, is reduced [88,101].…”
Section: Linked To CD [105]mentioning
confidence: 99%
“…One of the most important functions is production of short-chain fatty acids (SCFAs) by fermentation of undigested carbohydrates. These SCFAs have been depicted to regulate transepithelial transport [76], colonocyte proliferation and differentiation [77], mucosal inflammation [78,79], intestinal motility, and barrier function [80]. Many shortchain fatty acids (SCFAs) producing bacteria are decreased in IBD patients [51].…”
Section: Gut Flora and Inflammatory Bowel Diseasementioning
confidence: 99%